Maori identity and "political arithmetick" : the dynamics of reporting ethnicity - Kukutai, Tahu (2022)
Thesis (M. Soc.Sc. Demography)–University of Waikato, 2001. Includes bibliographical references (leaves 193-203)
Keywords: crown policy; ethnic identity; ethnicity

White Mothers, Brown Children: Ethnic Identification of Maori-European Children in New Zealand - Kukutai, Tahu H (Journal of Marriage and Family, 2007)
Studies of multiethnic families often assume the ethnic identification of children with the minority group results from the minority parent. This study examines an alternate view that mainstream parents also play an important role in transmitting minority ethnicity. It explores this argument using data from New Zealand on the ethnic labels mothers assign to their Maori-European children. It finds that European mothers are just as disposed as Maori mothers to designate their child as Maori, either exclusively or in combination. Two explanations, grounded in ethnic awareness and gendered inheritance, are proposed. Although neither satisfactorily predicts maternal designation decisions, the readiness of European mothers to identify their child as Maori underscores their role in diffusing Maori ethnicity.
Keywords: ethnic identity; ethnicity; interethnic marriage